Simulated microgravity and the antagonistic influence of strigolactone on plant nutrient uptake in low nutrient conditions. (December 2018) - Liu, Guowei; Bollier, Daniel; Gübeli, Christian; Peter, Noemi; Arnold, Peter; Egli, Marcel; Borghi, Lorenzo
Abstract Human-assisted space exploration will require efficient methods of food production. Large-scale farming in presence of an Earth-like atmosphere in space faces two main challenges: plant yield in microgravity and plant nutrition in extraterrestrial soils, which are likely low in nutrients compared to terrestrial farm lands. We propose a plant-fungal symbiosis (i.e. mycorrhiza) as an efficient tool to increase plant biomass production in extraterrestrial environments. We tested the mycorrhization of Solanaceae on the model plantPetunia hybrida using the arbuscular mycorrhizal fungusRhizophagus irregularis under simulated microgravity (s0-g ) conditions obtained through a 3-D random positioning machine. Our results show thats0-g negatively affects mycorrhization and plant phosphate uptake by inhibiting hyphal elongation and secondary branching. However, in low nutrient conditions, the mycorrhiza can still support plant biomass production ins0-g when colonized plants have increased SL root exudation. Alternatively, s0-g in high nutrient conditions boosts tissue-specific cell division and cell expansion and overall plant size inPetunia, which has been reported for other plants species. Finally, we show that the SL mimic moleculerac-GR24 can still induce hyphal branching in vitro under simulated microgravity. Based on these results, we propose that in nutrient limited conditions strigolactone root exudation can challenge the negative microgravity effects on mycorrhization and therefore might play an important role in increasing the efficiency of future space farming. Plant biology: Plant hormone promotes beneficial interactions with fungi in microgravity A plant hormone that regulates shoot branching and promotes symbiotic interactions with soil fungi can help crops overcome the negative effects of microgravity. A team led by Lorenzo Borghi from the University of Zurich, Switzerland, grew petunia flowering plants together with a beneficial fungus in simulated microgravity conditions. They showed that the lack of Earth-like gravity led to reduced production of mycorrhiza, a plant-fungal interaction known to help the plant absorb nutrients when low in soil. Plants that secrete high levels of this hormone, the carotenoid-derived strigolactone, can still thrive under microgravity conditions, as can fungi treated with a synthetic molecule that mimics the function of strigolactone. The findings could help inform best practices for space farming under the kinds of soil and environmental conditions present on space missions or on other planets.